Ronin overexpression induces cerebellar degeneration in a mouse model of ataxia - Thomas P. Zwaka; Marta Skowronska; Ronald Richman; Marion Dejosez (The Company of Biologists, 2021)
Spinocerebellar ataxias (SCAs) are a group of genetically heterogeneous inherited neurodegenerative disorders characterized by progressive ataxia and cerebellar degeneration. Here, we used a mouse model to test a possible connection between SCA and Ronin (Thap11), a polyglutamine-containing transcriptional regulator encoded in a region of human chromosome 16q22.1 that has been genetically linked to SCA type 4. We report that transgenic expression of Ronin in mouse cerebellar Purkinje cells leads to detrimental loss of these cells and the development of severe ataxia as early as 10 weeks after birth. Mechanistically, we find that several SCA-causing genes harbor Ronin DNA-binding motifs and are transcriptionally deregulated in transgenic animals. In addition, ectopic expression of Ronin in embryonic stem cells significantly increases the protein level of Ataxin-1, the protein encoded by Atxn1, alterations of which cause SCA type 1. This increase is also seen in the cerebellum of transgenic animals, although the latter was not statistically significant. Hence, our data provide evidence for a link between Ronin and SCAs, and suggest that Ronin may be involved in the development of other neurodegenerative diseases.